1978
DOI: 10.1007/bf01542062
|View full text |Cite
|
Sign up to set email alerts
|

Equity and extramarital sexuality

Abstract: Equity theory has recently been found to be a useful framework for understanding the effects of imbalances in intimate "contractual" relationships such as marriage. Equitable couples seem to be happier, more satisfied with their relationship, and more confident that it will last than are their more mismatched, i.e., inequitable, counterparts. Furthermore, inequitable couples predictably act to "set things right" in their marriage. They either restore actual equity to the relationship or psychologically set the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 5 publications
0
39
0
1
Order By: Relevance
“…Sprecher, 1986). Several scholars reported that the under benefited spouse (Prins, Buunk, & VanYperen, 1993;Walster, Traupman & Walster;, particularly women, were most "likely to engage in an extramarital relationship, often the first step to ending a marriage" (Buunk & Mutsaers, 1999, p 125). …”
mentioning
confidence: 99%
“…Sprecher, 1986). Several scholars reported that the under benefited spouse (Prins, Buunk, & VanYperen, 1993;Walster, Traupman & Walster;, particularly women, were most "likely to engage in an extramarital relationship, often the first step to ending a marriage" (Buunk & Mutsaers, 1999, p 125). …”
mentioning
confidence: 99%
“…51 The results suggest that having greater power does improve the quality of alternatives available and reduce commitment, as the principle of least interest would suggest, but also decreases satisfaction with the relationship. 52 Previous studies have found that equitable relationships are the most desirable 53 which is why Dunbar and Burgoon 54 speculated that the majority of their sample of married and cohabiting couples preferred characterizing their relationship as equal rather than unequal in power despite the differences in dominance behavior exhibited. Generally, the investment model has proved to be a useful tool for examining power relationships as they affect the stability and commitment of close relationships.…”
Section: Additional Theories Related To Social Exchangementioning
confidence: 99%
“…With reference to the equity theory (Walster et al, 1978) and investment model, briefly discussed by Drigotas and Barta (2012), pursuing an alternative relationship if positively evaluated may be considered as an equity restoration mechanism and may weaken the commitment to the marital relationship. The weakening of the commitment is due to the lessening of the marital as well as familial relationship satisfaction due to the unfulfilled needs and expectations of the woman, which in this study are also juxtaposed with the regard for children.…”
Section: Husband Versus Lover: On Perpetuating Factorsmentioning
confidence: 99%